The Effect of Glycemic Control on Plasma Ghrelin and Serum IGF-1 Levels in Type 1 Diabetic Girls - Tolga Altuğ Şen; Reşit Köken; Tevfik Demir; Ayşegül Bükülmez (Güncel Pediatri)
Introduction: The aim of this study was to investigate the effect of glycemic control on plasma ghrelin levels and serum IGF-1 levels in girls with type 1 diabetes. Materials and Method: The study group composed of 32 diabetic girls between the ages of 14.0-20.0 years with Tanner pubertal stage 5; and 15 healthy girls in similar ages with Tanner pubertal stage 5 formed the control group. Diabetic girls were classified as well glycemic controlled (n=18) and poor glycemic controlled (n=14) according to last year’s mean glycosylated hemoglobin levels. All subjects were tested for fasting plasma ghrelin and serum IGF-1 levels. Results: The mean fasting plasma ghrelin levels in girls with well controlled diabetes, in girls wtih poor controlled diabetes and in control group were 483.4±221.9 pg/ml, 310.7±110.2 pg/ml, 471.9±175.0 pg/ml respectively. The mean serum IGF-1 levels in girls with well controlled diabetes was 233.9±59.2 ng/ml, in girls with poor controlled diabetes 183.9±36.7 ng/ml, and in healthy controls 247.3±48.5 ng/ml. Plasma ghrelin levels and serum IGF-1 levels were similar in girls with well controlled diabetes and in the control group, however it was significantly supressed in those with poorly controlled diabetes. Conclusion: The metabolic control may be a determinative factor on plasma ghrelin and serum IGF-1 levels of type 1 diabetics. Plasma ghrelin and serum IGF-1 levels were similar in well glycemic controlled diabetics and control group, while they were suppressed in only poor glycemic controlled diabetics. (Journal of Current Pediatrics 2009; 7: 104-10)